Formation of the model for the commercialization of the company's digital intellectual assets - O. V. Loseva (Модернизация, инновация, развитие, 2024)
Purpose: of the study is algorithmic modeling of the commercialization of digital intellectual assets (CIAS), taking into account pricing factors, risk and the level of commercial potential, based on the identifi cation of CIAS and determination of their specifics.   Methods: general scientific methods of comparative analysis, systematization and generalization, identifi cation of distinctive features and price-forming factors that take into account the specifics of the objects of research are used. To form a model of the commercialization of digital intellectual assets, the algorithmic approach, the method of expert assessments in calculating the indicator of commercial potential, approaches and methods of valuation in determining the initial value of assets were used.Results: the author formulated the defi nition of a digital intellectual asset (DIA), establishes its relationship with related categories of assets, identifi es two categories of DIA indicating common and distinctive properties. Based on the results of the identifi cation of DIA, the factors aff ecting the value and commercial potential of various types of DIA are determined. The method for calculating the indicator of the commercial potential, taking into account the factors considered, is proposed. The tools of the commercialization, as well as approaches and methods of estimating the initial cost for various categories of DIA are disclosed. The algorithmic model of the DIA commercialization is constructed.   Conclusions and Relevance: the algorithmic model of commercialization of new types of assets, digital intellectual assets, proposed in the article takes into account their specifi cs and factors aff ecting the initial cost and commercial potential. The model can be used by Russian companies to increase their competitiveness in the context of the development of the digital rights and technologies market. Further research should be devoted to the specifi cation of the commercialization algorithm for certain categories of DIA: 1) intellectual property objects in digital form; 2) digital (digital utilitarian) rights to such objects and their use, implemented exclusively according to the rules of the information system (investment platform).